2004
DOI: 10.1161/01.hyp.0000114604.52270.95
|View full text |Cite
|
Sign up to set email alerts
|

Acromegalic Patients Show the Presence of Hypertrophic Remodeling of Subcutaneous Small Resistance Arteries

Abstract: Abstract-Structural alterations of small resistance arteries in patients with essential hypertension (EH) are mostly characterized by inward eutrophic remodeling. However, we have observed the presence of hypertrophic remodeling in patients with renovascular hypertension, as well as in patients with noninsulin-dependent diabetes mellitus, suggesting a relevant effect of humoral growth factors on vascular structure. Growth hormone may stimulate in vitro proliferation of vascular smooth muscle cells. However, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 21 publications
2
21
1
Order By: Relevance
“…We found a significant correlation between blood pressure and weight suggesting that the raised blood pressure was not a distinct pathological complication of acromegaly in the GH transgenic model but rather a reflection of the large animal phenotype. This is in agreement with previously published work in rodents and man [9,4,15,25,32]. Although, heart weight was increased in giant mice and reduced in dwarf mice, compared with control animals, the heart weight to body weight ratio was increased in giant mice but unchanged in dwarf mice.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found a significant correlation between blood pressure and weight suggesting that the raised blood pressure was not a distinct pathological complication of acromegaly in the GH transgenic model but rather a reflection of the large animal phenotype. This is in agreement with previously published work in rodents and man [9,4,15,25,32]. Although, heart weight was increased in giant mice and reduced in dwarf mice, compared with control animals, the heart weight to body weight ratio was increased in giant mice but unchanged in dwarf mice.…”
Section: Discussionsupporting
confidence: 93%
“…In a study using segments of small artery from patients with acromegaly, similar changes have been reported recently, as well as a statistically significant correlation between vascular morphology and plasma levels of IGF-1 [32]. Our data reinforce these findings because we report normal vascular structure in dwarf mice and significant correlations of structural parameters with body weight.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to patients with type 2 diabetes [Rizzoni et al 2005;Endemann et al 2004;Schofield et al 2002;Rizzoni et al 2001], hypertrophic remodeling of the small artery wall has also been found in renovascular hypertension [Rizzoni et al 1996] and acromegaly [Rizzoni et al 2004]. In figure 5, hypertrophic remodeling is associated with preservation of lumen size rather than a reduction.…”
Section: Control Subjects 2 Patients With Essential Hypertension 3 mentioning
confidence: 99%
“…Furthermore, the vascular consequences of acromegaly have been explored, demonstrating an increased intima-media thickness of common carotid arteries (4) and hypertrophic remodelling of subcutaneous small resistance arteries in acromegalic patients (5).…”
Section: Introductionmentioning
confidence: 99%